Modification and Performance of Log Periodic Dipole Antenna - Hamidi, Z.S.; Abidin, Z.Z.; Ibrahim, Z.A.; Shariff, N.N.M.; Monstein, C. (IJERD, 2012)
Technological advances and developments in solar activities, particularly in solar radio bursts, have created a demand of constructing log periodic dipole antenna (LPDA) to monitor this phenomenon in radio region. In this paper, we make an effort in designing a portable LPDA that suitable with the criteria, specification and practical enough although is the boom length size of the antenna is 3.11meter. This initiative is to modify so that it will be more portable and established enough. We choose value of 0.08 spacing factor τ= 0.8 as a directivity of antenna. The performance of this antenna will also be discussed.